Hubungan Lemak Subkutan dengan Kebugaran Jasmani Daya Tahan Otot pada Mahasiswa FKIK Universitas Warmadewa - I Gede Mandra Adnyana; Tanjung Subrata; Anny Eka Pratiwi (Aesculapius Medical Journal, 2024)
[The Relationship between Subcutaneous Body Fat and Physical Fitness Muscle Endurance in Students of the Faculty of Medicine and Health Sciences, Warmadewa University] Physical fitness is a collection of physical activities related to health or skills, where the level of fitness can be measured by certain physical tests. Muscular endurance is the ability of muscles to perform repeated contractions within a certain period of time. Fat content also has an important role in physical fitness, namely subcutaneous fat content. This is very necessary in daily activities, including medical students who need good physical fitness, especially when carrying out activities such as providing basic life support. This study aims to determine the relationship between subcutaneous fat levels and muscle endurance in students of the Faculty of Medicine and Health Sciences, Warmadewa University Batch 2021. This study used a correlational analytic research method with a cross-sectional study design. Subcutaneous fat content data was measured through measurements using a skinfold caliper which was carried out at four body locations, namely biceps, triceps, subscapula and suprailiac, while muscle endurance was measured using the sit up test and push up test. This study used a minimum sample size of 92 students who were taken using simple random sampling technique. Samples were analyzed using univariate analysis techniques and bivariate analysis using Spearman's test. The results showed that the correlation coefficient (r) was 0.395 (p=0.000) for the relationship between subcutaneous fat and muscle endurance sit-ups and the correlation coefficient (r) was 0.467 (p=0.000) for the relationship between subcutaneous fat content and muscle power. The conclusion of this study is that there is a relationship between subcutaneous body fat and physical fitness and muscle endurance in students of the Faculty of Medicine and Health Sciences, Warmadewa University batch 2021. It is recommended for batch 2021 student to control their subcutaneous body fat and performing exercise such as muscle endurance training in order to be able to perform cardiorespiratory rescucitation.